Neuropathy Caused by Metal Hypersensitivity after Placement of Stainless Steel Plate - Sunyarn Niempoog; Seksan Kukreja (Case Reports in Orthopedics)
Metal hypersensitivity is a rare complication for implants especially with neuropathy involvement. There was not any previous report suggesting metal hypersensitivity manifested in the form of neuropathy or tendinopathy from metal plate implantation. Here, we present a case of a 42-year-old female with chronic ulnar wrist pain and unremarkable physical and radiological findings. Ulna shortening osteotomy with small stainless steel-made DCP and screw fixation was done. On the third day postoperative, the patient developed pain, swelling, ulnar neuropathy, and flexor tendon contracture. Severe adhesion was found around the implant and the ulnar nerve. Minimal skin patch testing reaction and pathological study suggest a cell-mediated delayed type IV hypersensitivity reaction. A titanium-made LCP was later implanted in place of the stainless steel-made DCP. The patient’s clinical status significantly improved after the operation. Metal hypersensitivity in this patient was unprecedented and unique. The severity of the reaction and its location close to the ulnar nerve may predispose to the intensity of the reaction.